Marek Rona (1960-2012). Samorodny talent (Kronika Bydgoska, 2012)
Marek Rona - one of the most talented artists of Bydgoszcz - died in May 2012. He was one of the remarkably gifted artists with versatile fine arts interests. From the very beginning Bydgoszcz was the city of his life. For the city he created his most precious works, for example the reconstruction of the Sacred Heart monument in Poznański Sąuare (2010) - a symbol of gratitude for the return of Bydgoszcz to the motherland, the uniąue Way of the Cross based on the Shroud of Turin motifs with 15 big paintings, later given to a church in Gniezno, many plaques commemorating contacts of eminent Poles with Bydgoszcz, e.g. J.R. Wybicki - the author of the Polish national anthem, masks for the famous performance Szopka Bydgoska directed by editor Z. Pruss, and thousands of caricatures and satirical drawings. The artist deceased at a young age did not finish many works, e.g. the John Paul II monument in front of the Basilica Minor, and the famous musical elves.